Towards providing a more suitable housing for the low-income group : a study of the dwelling units of public low-cost flats in Kuala Lumpur, Malaysia - Noor Sharifah Sutan Sidi, 1950- (Nottingham : University of Nottingham, 1991)
Thesis (Ph.D) - University of Nottingham, 1991